Back Cover: Azido Pentoses: A New Tool To Efficiently Label Mycobacterium tuberculosis Clinical Isolates (ChemBioChem 13/2017). (20th June 2017) - Kolbe, Katharina; Möckl, Leonhard; Sohst, Victoria; Brandenburg, Julius; Engel, Regina; Malm, Sven; Bräuchle, Christoph; Holst, Otto; Lindhorst, Thisbe K.; Reiling, Norbert
Abstract : The back cover picture shows a new metabolic labeling method for Mycobacterium tuberculosis that uses azido pentoses. Mtb clinical isolates can be effectively illuminated in the presence of these synthetic carbohydrate derivatives, and this allows insight into the unknown worlds of the Mtb cell wall and its arabinan metabolism. Picture by K.K. More information can be found in the communication by T. K. Lindhorst, N. Reiling, et al. onpage 1172 in Issue 13, 2017 (DOI:10.1002/cbic.201600706 ).